2012
DOI: 10.1155/2012/301902
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofSalmonellaspp.,Candida albicans,Aspergillusspp., and Antimicrobial Residues in Raw and Processed Cow Milk from Selected Smallholder Farms of Zimbabwe

Abstract: A cross-sectional study was conducted to detect the presence of Salmonella spp., Candida albicans, Aspergillus spp., and antimicrobial residues in raw milk (n = 120) and processed cow milk (n = 20) from smallholder dairy farms from three sites in Zimbabwe. Culture and isolation of Salmonella spp., C. albicans, and Aspergillus spp. were performed using selective media, while antimicrobial residues were detected by a dye reduction test. No Salmonella, but C. albicans (17.5%; 21/120), Aspergillus spp. (0.8%; 1/12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
6
3
1
Order By: Relevance
“…The overall prevalence of 8.7% revealed by this study is lower than the 11.8% reported by Karns et al (2005). However, it is on the higher side when compared with the 2.6% and 0.0% reported by Van Kessel et al (2004) and Mhone et al (2012) respectively. These variations may be explained by the differences in location, hygienic practices and the availability of potable water.…”
Section: Prevalence Of Salmonella In Milk and Locally Processed Milk contrasting
confidence: 76%
“…The overall prevalence of 8.7% revealed by this study is lower than the 11.8% reported by Karns et al (2005). However, it is on the higher side when compared with the 2.6% and 0.0% reported by Van Kessel et al (2004) and Mhone et al (2012) respectively. These variations may be explained by the differences in location, hygienic practices and the availability of potable water.…”
Section: Prevalence Of Salmonella In Milk and Locally Processed Milk contrasting
confidence: 76%
“…Different other previous study recorded in Egypt was carried out in 2014, and the results revealed that (12%) of the milk samples were positive for Salmonella species by using the conventional culture methods [20] . On the other hand, the result of the present study is in contrast with the results of the previous studies obtained from [21,22] , who indicated that Salmonella species did not isolate and detect in examining raw milk samples.…”
Section: Discussioncontrasting
confidence: 99%
“…The absence of Salmonella enterica in 'brukina' may be attributed to the cold temperature (about 4 o C) they are kept for sale. Mhone et al (2012) examined 120 raw cow milk and 20 processed cow milk from smallholder dairy farms in Zimbabwe and found no Salmonella enterica. Similarly, to this study, Salmonella enterica were not found in 'brukina' but were found in the other samples examined.…”
Section: Resultsmentioning
confidence: 99%